1852 Terr. of N.M. Laws 66-69, § 3 - (:unkn) unknown (My University, 1852)
An Act Prohibiting the Carrying a Certain Class of Arms, within the Settlements and in Balls, § 3: Required those giving balls or fandangos to remove individuals armed with fire arms or other deadly weapons when liquor is sold.
Keywords: SENSITIVE PLACES